High glucose enhances HIV entry into T cells through upregulation of CXCR4. Issue 4 (1st October 2013) - Lan, Xiqian; Cheng, Kang; Chandel, Nirupama; Lederman, Rivka; Jhaveri, Aakash; Husain, Mohammad; Malhotra, Ashwani; Singhal, Pravin C.
Abstract : High glucose stimulates T cell ROS generation, which upregulates the expression of HIF‐1α and CXCR4, leading to the enhancement of HIV entry. Abstract : It is well known that patients with HIV are prone to diabetes mellitus because of the side effects of HARRT. However, whether high glucose affects the HIV infection of T cells is not clear. Recent studies have shown that upregulation of GLUT‐1 renders T cells susceptible to HIV infection. We hypothesized that hyperglycemia has the potential to increase HIV infection by enhancing its entry into immune cells. The effect of high glucose on HIV entry into T cells (Jurkat cells and PBMCs) and the mechanisms involved were investigated. High glucose significantly enhanced HIV entry, which was associated with increased T‐cell expression of CXCR4. However, T cells with silenced HIF‐1α displayed attenuated expression of CXCR4, whereas T cells with silenced CXCR4 showed decreased HIV entry in a high‐glucose milieu. On the one hand, high glucose stimulated T‐cell ROS generation, and H2 O2 at low concentrations enhanced the entry of HIV into T cells. On the other hand, inhibition of ROS not only attenuated high‐glucose–mediated T‐cell expression of CXCR4 and HIF‐1α but also mitigated T‐cell HIV entry in a high‐glucose milieu. In our study, high glucose enhanced HIV entry into T cells by increasing expression of CXCR4 and HIF‐1α.